Dezvoltarea conceptelor "virtual" şi "ideal" în cadrul predării fizicii [Articol] - Abramciuc, Valeriu (USARB, 2011)
In science, different concepts are accepted, reflecting the general, essential and necessary characteristics for a particular class of objects. Among them, in physics, the concepts of "virtual" and "ideal" have primary scientific and methodological values. In this paper, these concepts are presented and developed, based on a detailed analysis, followed by examples from various fields of physics. They should be taken into account in the process of teaching physics at different levels in setting intra- and interdisciplinary communication, in analyzing the effect on the formation of the scientific worldview, and others. Based on this, appropriate ways of competence formation will be developed: knowledge and understanding of physical phenomena, terminology, concepts, laws and practices that are specific to a particular area; experimental and theoretical scientific investigation, etc.
Keywords: ideal circuit elements; models; virtual; ideal; elemente ideale de circuit electric; modele; virtual; ideal